A Prospective Study of Blunt Trauma Abdomen in Pediatric Patients – Our Institutional Experience - Gurudatt Raipuria, Dinesh Kumar Barolia, Aditya Pratap Singh, Arun Kumar Gupta, Prameshwar Lal, Ajay Kumar, Mohan Lal, Rahul Gupta (Innovative Journal of Medical and Health Sciences, 2020)
Background – Blunt trauma abdomen is a significant cause of morbidity and mortality in pediatric patients because of their peculiar body habitus and immature musculoskeletal system. We aimed to study clinical presentations and outcome analysis of blunt trauma abdomen in children. Method - A prospective observational study from 16 October 2018 to 15 April 2020, carried out in our tertiary care teaching institute. Results – A total of 121 patients of less than 16 year age were included in this study. Male to female ratio was 4.26: 1. Most common age group was 6 – 12 years. Most common mode of injury was RTA (41.32%) followed by fall from height (27.27%). Liver was most commonly involved solid organ in our study (25.61 %). One hundred five patients (86.77%) were managed successfully with conservative management. Surgery was done 16 (13.22%) patients. Out of these 16 patients emergency surgery was done in 14 patients (11.57%). While 2 (1.65%) patients were planned for conservative treatment but ultimately they required surgery. Conclusion- Conservative treatment is an effective management modality in majority of pediatric blunt trauma abdomen patients without bowel perforation. Key Words: - Blunt trauma abdomen, Liver injury, Bowel injury, BTA, RTA.